Diet as a Risk Factor for Early-Onset Colorectal Adenoma and Carcinoma: A Systematic Review - Carroll, Kaitlin L.; Frugé, Andrew D.; Heslin, Martin J.; Lipke, Elizabeth A.; Greene, Michael W. (Frontiers in Nutrition, 2022)
Background: Colorectal cancer in adults 50 years old and younger is increasing in incidence worldwide. Diet may be a modifiable risk factor. The objective of this study was to examine evidence regarding the association between diet and the risk of developing early-onset colorectal cancer (EOCRC) and early-onset colorectal adenomas in young adults. Methods: PUBMED and Web of Science were systematically searched for studies examining dietary intake as a risk factor for EOCRC and early-onset colorectal adenomas. Results were synthesized narratively due to the heterogeneity of the studies. Results: Of the 415 studies identified, ten met the inclusion criteria. Of these ten studies, four provided data on dietary risk factors for early-onset colorectal adenomas and six provided data on dietary risk factors for EOCRC. The four studies that measured colorectal adenoma occurrence reported an increased incidence with high sugar sweetened beverage intake, a higher pro-inflammatory diet, a higher Western diet score and higher sulfur microbial diet score. A protective effect against early-onset colorectal adenomas was observed in those who had a higher Prudent diet score or higher adherence to other health dietary approaches (Dietary Approaches to Stop Hypertension, Alternative Healthy Eating Index-2010, or the alternative Mediterranean diet). Those who consumed large amounts of deep-fried foods, refined foods, followed a high fat diet, consumed large amounts of sugary drinks and desserts, and had low folate and fiber consumption had a significantly higher occurrence of EOCRC. A protective effect against EOCRC was observed for those who consumed more fruits and vegetables, high amounts of micronutrients and those who adhered to a vegetarian diet. Conclusions: The results of this study reveal various dietary habits may be risk factors or protective against early-onset colorectal cancer and adenomas. Future research should focus on large prospective cohort studies with long-term follow-up to confirm published results and further examine whether differences in diet quality are associated with EOCRC risk.